Prenatal diagnosis of transposition of great arteries with left anterior aorta (SDL-TGA) - Sujata S Alawani; Balaji Srimurugan; Brijesh Kottayil; Balu Vaidyanathan (Wolters Kluwer Medknow Publications, 2022)
We report a case with prenatal diagnosis of transposition of great arteries (TGA) with L-posed aorta (SDL-TGA) which was confirmed by postnatal echocardiography. The anatomic findings were confirmed during the successful arterial switch operation (ASO). The technical challenges of ASO in the L-posed aorta are also described.